2020
DOI: 10.3390/molecules25143303
|View full text |Cite
|
Sign up to set email alerts
|

One Hundred Faces of Geraniol

Abstract: Geraniol is a monoterpenic alcohol with a pleasant rose-like aroma, known as an important ingredient in many essential oils, and is used commercially as a fragrance compound in cosmetic and household products. However, geraniol has a number of biological activities, such as antioxidant and anti-inflammatory properties. In addition, numerous in vitro and in vivo studies have shown the activity of geraniol against prostate, bowel, liver, kidney and skin cancer. It can induce apoptosis and increase the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 117 publications
0
53
0
1
Order By: Relevance
“…Administration of coffee polyphenol extract significantly increases GLP-1 secretion in NCI-H716 and C57BL/6J mice associated with increasing intracellular cAMP levels in a dose-dependent manner [ 69 ]. Geraniol, an acyclic mnonoterpene alcohol extracted from the ethereal oils of aromatic plants, and citronellal, a specialized metabolite of plants found in Cymbopogon spp ., have a number of biological activities, such as antioxidant and antidiabetic properties [ 78 ]. Kim et al found that geraniol- and citronellal-stimulated GLP-1 secretion in NCI-H716 cells are mediated by the activation of olfactory receptor 1G1, the activation of Adcy, increased intracellular cAMP levels, and extracellular calcium influx.…”
Section: Gutmentioning
confidence: 99%
“…Administration of coffee polyphenol extract significantly increases GLP-1 secretion in NCI-H716 and C57BL/6J mice associated with increasing intracellular cAMP levels in a dose-dependent manner [ 69 ]. Geraniol, an acyclic mnonoterpene alcohol extracted from the ethereal oils of aromatic plants, and citronellal, a specialized metabolite of plants found in Cymbopogon spp ., have a number of biological activities, such as antioxidant and antidiabetic properties [ 78 ]. Kim et al found that geraniol- and citronellal-stimulated GLP-1 secretion in NCI-H716 cells are mediated by the activation of olfactory receptor 1G1, the activation of Adcy, increased intracellular cAMP levels, and extracellular calcium influx.…”
Section: Gutmentioning
confidence: 99%
“…Many studies have shown the antitumor activity of monoterpenes in cancer cells in vitro and in vivo through promoting cell cycle arrest, apoptosis, autophagy, and/or senescence [ 15 , 16 , 17 , 18 ]. The main anticancer mechanisms reported for these natural compounds include the inhibition of proteins involved in cell survival and proliferation (Ras, ERK, Akt), modulation of oxidative stress and endoplasmic reticulum stress, and depolarization of mitochondrial membrane potential [ 18 , 19 , 20 ]. In addition, it was reported increased anticancer activity of antineoplastic drugs combined with monoterpenes, suggesting their potential as novel anticancer molecules also employed as sensitizer compounds [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been conducted to gain insights into its anti-cancer activity [112][113][114]. Ornithine decarboxylase (ODC) plays a prime role in the synthesis of polyamines, providing stabilization to DNA structure [132]. A decrease in ODC activity after geraniol treatment has been observed in the intestinal adenocarcinoma Caco-2 cell line, which, in turn, caused DNA synthesis inhibition and cell cycle arrest in the S phase [132].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Ornithine decarboxylase (ODC) plays a prime role in the synthesis of polyamines, providing stabilization to DNA structure [132]. A decrease in ODC activity after geraniol treatment has been observed in the intestinal adenocarcinoma Caco-2 cell line, which, in turn, caused DNA synthesis inhibition and cell cycle arrest in the S phase [132]. Polyamine metabolism is a potential target in the development of cancer-preventive drugs, therefore, geraniol mediated decline in ODC activity might have a useful clinical role [133].…”
Section: Anticancer Activitymentioning
confidence: 99%